Export and Economic Growth Dynamics in Uganda - Mwebaze, Thomas; Buyinza, Faisal (ResearchSquare, 2022)
This article examines the relationship between economic growth and exports in Uganda using annual time series data and in the ARDL framework. The study provides evidence on the short and long run relationship between economic growth and exports and tests the export-growth-led hypothesis for Uganda. Our results reveal that exports significantly promote both short-run and long run economic growth in Uganda within the study period. Secondly, the results adjustment coefficient is negative and statistically significant, implying that there is a long-run relationship between exports and economic growth. Also, the adjustment coefficient indicates that the speed of adjustment to equilibrium is about 86% in case of any shock to the economy. In addition, our results show that foreign exchange rate, inflation and trade openness have a significant and negative effect on economic growth while private credit and capital formation have a positive and significant effect on long-run economic growth rate in Uganda. On the other hand, gross capital formation, private sector credit and exchange rate growth have a positive and significant effect on economic growth rate in Uganda in the short run. The findings of this study suggest that there is need for increased government commitment to boost production and quality of exports in order to exploit the untapped export potentials of the country. Secondly, government needs to put in place measures to ensure efficient utilization of external resources and a clear road map for trade openness. Finally, government should also put in place sound investment policies like ease of access to affordable credit plus stable macroeconomic conditions in form of low inflation and a stable exchange rate in order to stimulate economic growth that will further boast the country’s overall growth and development potentials.
Keywords: Exports, Economic growth, adjustment coecient, time series, Uganda